(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Biopsy in simple terms means removal of a tissue from a living person for diagnostic purposes. It helps indifferentiating an abnormal tissue from a normal one. It helps in diagnosis of various cancers, tumors or any unidentified growth seen during clinical examination.To evaluate the different types of intraoral biopsy procedures performed in an institutional setup in 1 year. It is designed as a retrospective study. A total of 234 patient records who had a growth intraorally and required investigation for the same were acquired. It was done analysing records of 86000 patient data who were treated from March 2019- March 2020. Descriptive statistics were used to analyse the frequency and percentage of the different intraoral biopsies performed. Chi square test was used to evaluate the correlation between age and gender with the different types of biopsy procedures performed. SPSS version 20 software was used to perform statistics.Out of the total data extracted, 80.3 percent underwent incisional biopsy, in 17.5% excisional biopsy was carried out, 1.3% underwent FNAC procedures and 0.9% other biopsy techniques were performed. Maximum biopsy procedures were carried out between the age group of 40- 60 years. More cases were seen among the male population. Age had a positive relation with the type of biopsy performed when chi square test was done p value less than 0.05. Gender a negative correlation with the type of biopsy performed p value more than 0.05.Incisional biopsy was found to be the most commonly performed type of biopsy. Age had a positive correlation with the type of biopsy performed. Gender did not have a significant correlation with the type of biopsy performed.